Pharmacological activities, mechanisms of action, and safety of salidroside in the central nervous system - Zhong ZF; Han J; Zhang JZ; Xiao Q; Hu J; Chen LD (Dove Medical Press, 2018)
Zhifeng Zhong,1 Jing Han,1 Jizhou Zhang,1 Qing Xiao,1 Juan Hu,1,2 Lidian Chen1,2 1Institute of Materia Medica, Fujian Academy of Traditional Chinese Medicine, Fuzhou, Fujian, People’s Republic of China; 2School of Rehabilitation Medicine, Fujian University of Traditional Chinese Medicine, Fuzhou, Fujian, People’s Republic of China Abstract: The primary objective of this review article was to summarize comprehensive information related to the neuropharmacological activity, mechanisms of action, toxicity, and safety of salidroside in medicine. A number of studies have revealed that salidroside exhibits neuroprotective activities, including anti-Alzheimer’s disease, anti-Parkinson’s disease, anti-Huntington’s disease, anti-stroke, anti-depressive effects, and anti-traumatic brain injury; it is also useful for improving cognitive function, treating addiction, and preventing epilepsy. The mechanisms underlying the potential protective effects of salidroside involvement are the regulation of oxidative stress response, inflammation, apoptosis, hypothalamus-pituitary-adrenal axis, neurotransmission, neural regeneration, and the cholinergic system. Being free of side effects makes salidroside potentially attractive as a candidate drug for the treatment of neurological disorders. It is evident from the available published literature that salidroside has potential use as a beneficial therapeutic medicine with high efficacy and low toxicity to the central nervous system. However, the definite target protein molecules remain unclear, and clinical trials regarding this are currently insufficient; thus, guidance for further research on the molecular mechanisms and clinical applications of salidroside is urgent. Keywords: salidroside, Alzheimer’s disease, Parkinson’s disease, stroke, cognitive impairment, clinical trials